Flow cytometry and K-mer analysis estimates of the genome sizes of Bemisia tabaci B and Q (Hemiptera: Aleyrodidae) - Guo, Li T.; Wang, Shao L.; Wu, Qing J.; Zhou, Xu G.; Xie, Wen; Zhang, You J. (Frontiers in Physiology, 2015)
The genome sizes of the B- and Q-types of the whitefly Bemisia tabaci (Gennnadius) were estimated using flow cytometry (Drosophila melanogaster as the DNA reference standard and propidium iodide (PI) as the fluorochrome) and k-mer analysis. For flow cytometry, the mean nuclear DNA content was 0.686 pg for B-type males, 1.392 pg for B-type females, 0.680 pg for Q-type males, and 1.306 pg for Q-type females. Based on the relationship between DNA content and genome size (1 pg DNA = 980 Mbp), the haploid genome size of B. tabaci ranged from 640 Mbp to 682 Mbp. For k-mer analysis, genome size of B-type by two methods were consistent highly, but the k-mer depth distribution graph of Q-type was not enough perfect and the genome size was estimated about 60M larger than its flow cytometry result. These results corroborate previous reports of genome size based on karyotype analysis and chromosome counting. However, these estimates differ from previous flow cytometry estimates, probably because of differences in the DNA reference standard and dyeing time, which were superior in the current study. For Q-type genome size difference by two method, some discussion were also stated, and all these results represent a useful foundation for B. tabaci genomics research.